Modos de provisão em habitação social nos assentamentos urbanos : à prática do Núcleo Social Papa João XXIII - Takano, Edna Satie Abe (2009)
It is possible to adopt effective strategies for the solution of Housing demand through the prioritization of actions that characterize the social Housing as part of a planning process that values the man as a citizen and individual, and Housing not only as a product but as a place for a human being to develop socially, economically, politically and emotionally. At the Social Center Papa João XXIII, located in the city of Maringá - Paraná, seventy two units ready to be rented are considered part of a program whose aims are to help people own a house, to promote restoration of family and social bonds as well as to promote education for the families involved, that is, it is a program that enhances the social role of Housing. Besides establishing the diagnosis, the objective of this paper is to analyze an experience concerning social Housing provision which can be followed in order to improve the experiences tracked. In this study, components of the provision process are depicted. In addition, they also analyze and check the Housing unit, the satisfaction of the residents, access to infrastructure, to urban services and private essential services. This is an intrinsic case study in which the research site and provision process are based on exploratory research. Concerning the product, the indicative level of Post Occupancy based on semistructured interview was used. It can be assumed that the objective of the program is not only to help people become house owners but also it aims at including them in the society they live, which is a right everyone has.